Reverse Design of a Novel Coupling Strut for Vibration Attenuation in the Helicopter Cabin - Ming Ding; Jinhui Jiang; Fang Zhang; Xiao Liang; Nansun Shen (Aerospace, 2022)
Helicopter gearbox support strut is one of the main research objects in the field of vibration and noise control in helicopter cabins. Aiming to further widen the vibration attenuation range of traditional Bragg periodic struts, a novel type of Local resonance (LR)/Bragg coupling periodic strut with graded parameters as well as the reverse design method is proposed. Combined with the spectral element method (SEM) and the transfer matrix method (TMM), the analytical expression of the transform relationship of longitudinal vibrations through the coupling strut is yielded. The impacts of different parameters on the boundaries of bandgaps are explored according to the results of simulation analysis. On this basis, the gradient of parameters is determined, and then all unknown structural parameters can also be determined. Compared with the traditional Bragg periodic struts and the LR/Bragg coupling periodic strut with non-graded parameters, the presented strut has an obvious advantage of widening the low-frequency bandgaps below 500 Hz.